ЗАЛЕЖНІСТЬ ЕНЕРГЕТИЧНИХ ПРОЦЕСІВ ВИСОКОВОЛЬТНИХ ЕЛЕКТРОРОЗРЯДНИХ СВЕРДЛОВИННИХ КОМПЛЕКСІВ "СКІФ" ВІД ХАРАКТЕРИСТИК НАВАНТАЖЕННЯ - Хвощан, О.В.; Смірнов, О.П. (Інститут електродинаміки НАН України, Київ, 2022)
The work determines the dependences of electrical parameters of the ground and submerged parts of the charging unit of the electric-discharge borehole complex "Skif-100M" on peculiarities of changing of electrical characteristics of the active and reactive load contributed by modern geophysical cables up to 10 km long with an active resistance from 24 to 644 Ohm, capacitance from 0.2 to 1.8 μF and inductance from 2.9 to 31 mH. New dependences and conditions to increase the charging power of storage capacitor, the output power of the complex and the voltage of ground part of its power supply from load parameters were determined on the basis of analysis of transients in the charging circuit of a complex. There were realized necessary energy characteristics for creation of a universal submersible charging unit to increase energy efficiency and productivity of high-voltage borehole electric-discharge complexes of "Skif" type. The obtained results provide effective modernization of the domestic submersible electric-discharge equipment of such complexes (in particular, their ground power sources and submersible charging units). This extends the scope of their application in the oil and gas industry of Ukraine and increases the attractiveness of investment of foreign companies engaged in the processing of oil wells in different countries of the world to the Ukrainian economy. References 11, figures 4, tables 3.